Prosedur Penggajian Karyawan pada PT. Berkah Mawla Nafiah (BMN) Group di Kota Surabaya - Vidi Astutik; Priyo Utomo (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the payroll process that occurs at PT. BMN GROUP in the city of Surabaya. The data collection methodology uses a descriptive method and then analyzed using a certain method which produces a picture of something by utilizing qualitative data. Payroll system at PT. Berkah Mawla Nafiah (BMN) Group is based on calculations based on the total number of employee working hours per day, then salaries will be paid every month by multiplying the total number of working hours in one month by the total employee salary per day using Excel to find a global calculation. In providing employee salaries, updates using the payroll application are needed to facilitate employee salary calculations as a form of modernization effort in the employee payroll process so as to create effective and efficient payroll procedures.